The European Investment Bank and SMEs : key lessons for Latin America and the Caribbean - Griffith-Jones, Stephany (UN ECLAC SantiagoCL, 2011)
Discusses the engagement of the European Investment Bank Group (EIB Group) with the financing and support of SMEs, both within the European Union as well as EU Candidate Countries and the Balkans. Describes and analyses the practices and experiences of the EIB Group, discusses the key lessons and makes policy recommendations to be considered within the Latin America and Caribbean context.